2011
DOI: 10.1073/pnas.1012941108
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of developmental birdsong learning from the subsyllabic scale to cultural evolution

Abstract: Quantitative analysis of behavior plays an important role in birdsong neuroethology, serving as a common denominator in studies spanning molecular to system-level investigation of sensory-motor conversion, developmental learning, and pattern generation in the brain. In this review, we describe the role of behavioral analysis in facilitating cross-level integration. Modern sound analysis approaches allow investigation of developmental song learning across multiple time scales. Combined with novel methods that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 75 publications
2
33
0
Order By: Relevance
“…Characterizing the temporal structure of a behavior is necessary to understand how the brain learns and generates the timing of behavioral sequences (Lipkind and Tchernichovski, 2011). We found that syllable durations in young birds are exponentially-distributed, indicating an extreme level of randomness in the syllable generation process.…”
Section: Discussionmentioning
confidence: 99%
“…Characterizing the temporal structure of a behavior is necessary to understand how the brain learns and generates the timing of behavioral sequences (Lipkind and Tchernichovski, 2011). We found that syllable durations in young birds are exponentially-distributed, indicating an extreme level of randomness in the syllable generation process.…”
Section: Discussionmentioning
confidence: 99%
“…The bird finally produces a crystallized song, which is characterized by temporal and spectral stereotypy, at the time of sexual maturity. The process of developmental song learning has been extensively studied, and numerous detailed reviews are available (e.g., Marler 1997;Margoliash 2002;Lipkind and Tchernichovski 2011).…”
Section: Sleep and Developmental Song Learning In Zebra Finchesmentioning
confidence: 99%
“…2A,B). This transition has been studied extensively at both behavioral and neuronal levels (Aronov et al, 2008;Lipkind and Tchernichovski, 2011), and we suggest that it facilitates both vocal learning and song culture: the wide and continuous range of early vocal babbling is optimal for vocal exploration, namely for matching the 'sensory templates' of song syllables produced by an adult bird 'tutor'. As song imitation progresses during development, distinct syllable types (clusters) emerge and differentiate (Fig.…”
Section: How Song Learning Sustains Polymorphic Dialectsmentioning
confidence: 99%